Upaya Meningkatkan Teknik Dasar Pasing Atas Bola Voli Mini melalui Bantuan Tutor Sebaya Siswa kelas IV SD Negeri Balongwono Kecamatan Trowulan Kabupaten Mojokerto Tahun 2018/2019 - Sugemi (PROGRESSA: Journal of Islamic Religious Instruction, 2020)
Physical education is basically an integral part of the education system as a whole which aims to develop aspects of health, physical fitness, critical thinking skills, emotional stability, social skills, reasoning and moral action through physical activities and sports. The purpose of this study was to improve learning outcomes for grade V SD Negeri Balongwono, Trowulan District, Mojokerto Regency through the assistance of peer tutors. The research was conducted at SD Negeri Balongwono, Trowulan District, Mojokerto Regency in the first semester of the 2018/2019 academic year, from March 2019 to April 2019. The subjects of this study were GRADE V SD Negeri Balongwono, Mojokerto Regency in the 2018/2019 academic year, namely 26 people who above: 16 boys and 10 girls. Sources of data used in Graderoom Action Research (PTK) are as follows: 1. Data on learning outcomes above, obtained from students; 2. Teacher activity data, obtained from events during the teaching and learning activities in progress; 3. Student activity data, obtained from events during the teaching and learning activities; 4. Data on the implementation of teaching and learning activities with the help of peer tutors, obtained from events during the teaching and learning activities. The data analyzed included quantitative data (by presenting numbers as a measure of achievement), and qualitative data (presenting numbers as a comparison). Data analysis was carried out in a descriptive comparative manner which aims to compare the conditions before and after the learning corrective action was taken. The stages in the action of analyzing data include data reduction, data presentation, and drawing conclusions. Based on the data analysis of the basic technique of passing on mini volleyball for Grade V students of SD Negeri Balongwono, Trowulan District, Mojokerto Regency, 2018/2019 academic year, the following results can be obtained: 1. In the pre-action of 26 students, there were 11 students (42%) who completed learning. 2. At the end of the first cycle of 26 students, there were 19 students (73%) who had finished learning. 3. At the end of the second cycle of 26 students, 23 students (88%) have completed learning. Thus it can be concluded that the application of the peer tutor assistance method can improve the basic techniques of fitting for the V-grade mini volleyball of the V-grade students of SD Negeri Balongwono, Trowulan District, Mojokerto Regency, 2018/2019 Academic Year.